2021
DOI: 10.1007/s11242-021-01586-2
|View full text |Cite
|
Sign up to set email alerts
|

Permeability Estimation of Regular Porous Structures: A Benchmark for Comparison of Methods

Abstract: The intrinsic permeability is a crucial parameter to characterise and quantify fluid flow through porous media. However, this parameter is typically uncertain, even if the geometry of the pore structure is available. In this paper, we perform a comparative study of experimental, semi-analytical and numerical methods to calculate the permeability of a regular porous structure. In particular, we use the Kozeny–Carman relation, different homogenisation approaches (3D, 2D, very thin porous media and pseudo 2D/3D),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
(62 reference statements)
0
26
0
Order By: Relevance
“…Through the definition of 𝐽 𝑆 , the formulation in Equation (36) becomes 𝑛 𝑆 = 𝑛 𝑆 0𝑆 𝐽 −1 𝑆 . With linearization, the relationship yields the following:…”
Section: Appendix A: Unified Unsaturated/saturated Porous Media Conti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Through the definition of 𝐽 𝑆 , the formulation in Equation (36) becomes 𝑛 𝑆 = 𝑛 𝑆 0𝑆 𝐽 −1 𝑆 . With linearization, the relationship yields the following:…”
Section: Appendix A: Unified Unsaturated/saturated Porous Media Conti...mentioning
confidence: 99%
“…34,35 where an idealized micro-geometry of the pore network was considered. To estimate the permeability of a benchmark periodic porous structure, Wagner et al 36 compared in an upscaling study the results of the Kozeny-Carman equation, various homogenization methods, pore-scale simulations (including LBM), and pore-scale experiments. In their work, they concluded that the homogenization and pore-scale models provided accurate permeability results, whereby the Kozeny-Carman relation did not provide acceptable permeability results and the pore-scale experiments yielded underestimated values.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of permeability prediction, the labeling process of geological specimens is connected to the computation of 3D stationary flow fields of a single-phase fluid within the pore space. For permeability prediction under regular geometries, a broader set of methods is available as described and compared in [9].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, our forward simulation is based on a distributed-parallel Stokes solver utilizing the finite element library MFEM [20]. As studied in [9] for simple cylindrical obstacles, such DNS approaches (in this case FEM) deliver results comparable to LBM. However, our implementation successfully alleviates the drawback of an impractically large number of iterations to obtain the desired accuracy on complex geometries.…”
Section: Introductionmentioning
confidence: 99%
“…Kozeny-Carman, or determined by means of numerical upscaling techniques, e.g. [27,55,64] and references therein. However, the permeability is uncertain in general.…”
mentioning
confidence: 99%